PUBLIC SERVICE ANNOUNCEMENT IN HEALTHCARE: LINGUISTIC AND STYLISTIC FEATURES AS A REFLECTION OF SOCIETAL CHANGE - Natalia P. Chikunova; Liliia K. Khalitova (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. The study of the linguistic and stylistic features of public service announcement (PSA) is of considerable interest from the point of view of analyzing the changes in linguistic and stylistic means reflecting social transformations. Social advertising, being a means of mass communication, is sensitive to current social demands and cultural changes, which allows one to identify the features of its linguistic design in different historical periods. The study of such texts provides an opportunity for a deeper understanding of both the language system and the sociocultural context in which PSA functions, as well as the dynamics of changes in social values and priorities.